2006
DOI: 10.1590/s0004-282x2006000600026
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine dysregulation syndrome in Parkinson's disease: case report

Abstract: -We report a 67-year-old man with Parkinson's disease for 9 years who developed compulsive use of levodopa. This phenomenon is the main feature of the dopamine dysregulation syndrome. Other related symptoms presented by our patient were mood fluctuation and increased writing activity suggestive of punding.KEY WORDS: Parkinson's disease, dopamine dysregulation syndrome, punding.Síndrome de desregulação dopaminérgica na doença de Parkinson: relato de caso RESUMO -Relatamos sobre um homem de 67 anos de idade com … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 18 publications
0
33
0
2
Order By: Relevance
“…Despite the limited evidence regarding therapy of ICD and DDS, it is generally indicated adjustment of dopaminergic therapy, behavioral and pharmacological therapy used in ICD without PD, and psychosocial support 63 . These patients present a challenge to the clinician 64 . There are case reports of successful treatment of ICD in DP with clo-zapine, quetiapine, valproate, lithium, topiramate, donepezil, amantadine, cyproterone (for hypersexuality), and deep brain stimulation 65 .…”
Section: Impulse Control Disorders and Dopamine Dysregulation Syndromementioning
confidence: 99%
“…Despite the limited evidence regarding therapy of ICD and DDS, it is generally indicated adjustment of dopaminergic therapy, behavioral and pharmacological therapy used in ICD without PD, and psychosocial support 63 . These patients present a challenge to the clinician 64 . There are case reports of successful treatment of ICD in DP with clo-zapine, quetiapine, valproate, lithium, topiramate, donepezil, amantadine, cyproterone (for hypersexuality), and deep brain stimulation 65 .…”
Section: Impulse Control Disorders and Dopamine Dysregulation Syndromementioning
confidence: 99%
“…The core features of DDS are self-medication, levodopa-seeking and hoarding associated with disabling mood and behavioral changes. 3 In DDS, mood dysregulation comprises alternation between depressed and elated affect, and is frequently associated with hypersexuality, aggression, pathological gambling, compulsive shopping and social isolation, resembling a bipolar-like syndrome. [2][3][4] An additional behavioral disorder supposedly associated with changes in dopaminergic neurotransmission is punding, which consists of repetitive, stereotyped, aimless and disrupted behaviors related to the person's past work or hobby.…”
Section: Introductionmentioning
confidence: 99%
“…3 In DDS, mood dysregulation comprises alternation between depressed and elated affect, and is frequently associated with hypersexuality, aggression, pathological gambling, compulsive shopping and social isolation, resembling a bipolar-like syndrome. [2][3][4] An additional behavioral disorder supposedly associated with changes in dopaminergic neurotransmission is punding, which consists of repetitive, stereotyped, aimless and disrupted behaviors related to the person's past work or hobby. 5,6 In a previous study by our group we found that the lifetime frequency of bipolar I and II disorders in PD seems to be similar to that observed in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Information on these conditions are rare in Brazilian patients 17 . Thus, we believe it is underreported in Brazilian literature, due to the fact that there have not been any valid instruments to identify ICDs in affected individuals.…”
Section: Discussionmentioning
confidence: 99%